Protection of Women and Children in the Perspective of Legal Pluralism: A Study in Aceh and West Nusa Tenggara - Zainuddin, Muslim; Nyak Umar, Mukhsin; Sumardi, Dedy; Mansari, Mansari; Khalil, Zakki Fuad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
The coexistence of Islamic law, customary law, and the national legal system within empirical societies remains an ongoing phenomenon. The consequences of such legal pluralism have implications for the protection of women and children. This study aims to examine the dynamics of legal relationships, the determination of diverse laws among the people of Aceh and West Nusa Tenggara, and the factors influencing the contestation of legal choices that impact legal favoritism towards women and children. This study employed a juridical empirical legal research method with a legal pluralism approach. Data were obtained by means of in-depth interview and document study. The interviews were conducted with customary leaders, religious leaders, and academics, whilst document analysis included journal articles, laws, and relevant books. The study took place in two locations: Aceh and West Nusa Tenggara Provinces. The findings of the study reveal that the dynamics of the relationship between customary law, religious law, and state law run concurrently in the context of the application of family law and criminal law. Some members of the community follow customary law and religious law, while others follow state law. The determination of law among the people of Aceh and Lombok is based on the legal consciousness of the community concerned. The choice of law in societal reality has an impact on favoritism towards women and children. The choice of state law tends to guarantee legal certainty and can provide legal protection for women and children. Conversely, the choice of religious law and customary law may sometimes be detrimental to women and children.